The Neotropical green lacewing genus Ceraeochrysa Adams (Neuroptera: Chrysopidae)—new synonymies and combinations, a new species, and an updated key to species - Sosa-Duque, Francisco José; Tauber, Catherine A. (Zootaxa, 2021)
Ceraeochrysa Adams, 1982, with 60 species, is a diverse and relatively well studied New World genus of green lacewings. However, nomenclatural problems and misidentifications persist; undescribed species continue to be found; and species determinations remain difficult. Here, we address several problematic issues within the genus, and we justify the following taxonomic changes: Part 1 synonymizes Ceraeochrysa rafaeli Adams & Penny syn. n. and Chrysopodes (Chrysopodes) nigropictus Freitas & Penny syn. n. with Ceraeochrysa discolor (Navás). Part 2 identifies Ceraeochrysa adynatos (Freitas & Penny) comb. n. as the new name for Chrysopodes (Chrysopodes) adynatos Freitas & Penny. Part 3 renames Chrysopa sarta Banks as Ceraeochrysa sarta (Banks) comb. n, and identifies it as conspecific with Ceraeochrysa berlandi (Navás) syn. n. Part 4 names Chrysopa poujadei Navás as Ceraeochrysa poujadei (Navás) comb. n. and also identifies its new synonyms—Chrysopodes (Chrysopodes) laevus (Navás) syn. n. and Ceraeochrysa forcipata Freitas & Penny syn. n. Part 5 redescribes the enigmatic Ceraeochrysa silvanoi (Navás) and recognizes Ceraeochrysa tucumana (Navás) syn. n. as its junior synonym. Part 6 describes a new Ceraeochrysa species: Ceraeochrysa paraensis Sosa sp. n. from Brazil. Finally, to help facilitate species identifications, Part 7 incorporates all new species and all taxonomic changes made since the last revision of the genus (2009) into an updated key to the currently valid species of Ceraeochrysa. Lectotypes are designated for three species: C. discolor Navás, C. sarta Banks, and C. tucumana Navás.